Improving Pepper Inbreds for Resistance to Pepper Yellow Leaf Curl Thailand Virus (PepYLCTHV) through Challenged Inoculations - Nattika Kumsee; Patcharaporn Suwor; Montinee Teerarak; Wen-Shi Tsai; Suchila Techawongstien; Tanyarat Tainta; Sanjeet Kumar; Nakarin Jeeatid; Orawan Chatchawankanphanich; Somsak Kramchote (My University, 2024)
Chili peppers (Capsicum annuum L.) are economically important crop worldwide. Pepper yellow leaf cure Thailand virus (PepYLCTHV), a Begomovirus causing yellow leaf mosaic disease of chili pepper has been reported to damage 95% economic loss under favorable epidemic conditions. Thirty-one chili genotypes were screened for resistance to PepYLCTHV disease through challenge inoculation using 10-15 viruliferous whiteflies per plant. We purified two resistant lines (PEP6 and PEP12) through four generations of selfing and selection through challenged inoculations. At the 28 days after inoculations two chili genotypes showed symptoms less based on disease severity and percentage of disease incidence of 30 plants PEP6 showed a disease severity 3.64 with 69.33 % DI and PEP12 showed a disease severity 3.83 with 77.67 % DI. PEP6 and PEP12 were selected for pure-line development for four cycles.Both varieties showed an increase in percentage of the resistant plant 12.78 % and 16.77 %, respectively. These lines have potential for release as resistant lines for improvement chili pepper resistance to PepYLCTHV and for developing maker associated with the resistant trait.
Keywords: Chili pepper; Leaf curl; Plant Virus Research Studies